Geology of the High Sillaro Valley (Northern Apennines of Italy). Issue 2 (9th December 2020) - Panini, Filippo; Bettelli, Giuseppe; Carlini, Mirko; Fioroni, Chiara; Nirta, Giuseppe; Remitti, Francesca
ABSTRACT: We map the High Sillaro Valley, in the Northern Apennines of Italy. Here the Ligurian wedge overthrust the foredeep deposits of the Marnoso Arenacea formation – MA. The overthrusting occurred through a shear zone with components derived from the frontal part of the Ligurian wedge and interpreted as a tectonic mélange (Sestola-Vidiciatico Tectonic unit - SVU) here subdivided into two different subunits structurally independent one from the other. In the area, the Visignano chaotic body (VIS) constitutes an intercalation within the Serravallian-Tortonian MA and derives, as the SVU, from the frontal part of the Ligurian wedge. We performed a detailed investigation of the components of the VIS that helps to better define the architecture of the frontal part of the Ligurian wedge and to constrain the timing of the deformation phases affecting this portion of the Northern Apennines during the middle-late Miocene.